Optimization of Environmental and Defense of the New Capital City ‘Nusantara’ Based on Pancasila and SDGs - Xavier Nugraha; Krisna Angela; Natasha Caecilia Lisanggraeni Rositaputri; Amilah Fadhlina (Fakultas Hukum, Universitas Internasional Batam, 2022)
The development and industrialization of the new capital city